2014
DOI: 10.1021/pr500492j
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Quantitative Proteomic Profiling Identifies Disruption of Ubiquitin Homeostasis As a Key Driver of Schwann Cell Defects in Spinal Muscular Atrophy

Abstract: Low levels of survival of motor neuron (SMN) protein cause the neuromuscular disease spinal muscular atrophy (SMA), characterized by degeneration of lower motor neurons and atrophy of skeletal muscle. Recent work demonstrated that low levels of SMN also trigger pathological changes in Schwann cells, leading to abnormal axon myelination and disrupted deposition of extracellular matrix proteins in peripheral nerve. However, the molecular pathways linking SMN depletion to intrinsic defects in Schwann cells remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 29 publications
(79 reference statements)
1
26
0
Order By: Relevance
“…Taken together, these findings support the hypothesis that myelination defects in SMA result from direct, intrinsic deficiencies in Schwann cells, rather than occurring as a secondary consequence to pathology in neighbouring motor neurons (32,33). …”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Taken together, these findings support the hypothesis that myelination defects in SMA result from direct, intrinsic deficiencies in Schwann cells, rather than occurring as a secondary consequence to pathology in neighbouring motor neurons (32,33). …”
Section: Resultssupporting
confidence: 78%
“…Glial cells from the peripheral nervous system (PNS) have also been implicated in SMA, with changes observed in non-myelinating terminal Schwann cells in several different SMA mouse models (29–31). Similarly, in vivo and in vitro analyses of myelinating Schwann cells demonstrated intrinsic defects in SMA (evidenced by SMN-dependent failure of isolated SMA-derived Schwann cells to respond to myelination cues), leading to defects in myelination and generation of extracellular matrix in peripheral nerve (32,33). …”
Section: Introductionmentioning
confidence: 99%
“…To understand how SMN deficiency can disrupt Schwann cell physiological functions, Sarvestany and collaborators (2014) (Table 1) performed label-free proteomics analyses of Schwann cells obtained from SMA mouse peripheral nerve [90]. Through this approach, they found that several pathways were altered in SMA Schwann cells including growth, proliferation, cell death, survival and molecular transport.…”
Section: Other Cell Types Outside the Central Nervous System Involmentioning
confidence: 99%
“…Of particular interest, functional cluster analysis revealed that ubiquitination pathways are profoundly disrupted in SMN-deficient Schwann cells. For example, reduced levels of ubiquitin-like modifier activating enzyme 1 (uba1) were observed [90]. In fact, suppression of Uba1 through pharmacological treatment in WT Schwann cells is sufficient to recapitulate the defective myelination phenotype presented by SMA Schwann cells [90].…”
Section: Other Cell Types Outside the Central Nervous System Involmentioning
confidence: 99%
See 1 more Smart Citation